Hubungan Praktik Pemberian Makanan Pendamping-ASI dengan Kejadian Stunting pada Balita - Atalia Pili Mangngi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Stunting remains a major nutritional problem in Indonesia, impacting the quality of human resources. One important factor contributing to stunting is child feeding practices, especially during the First 1,000 Days of Life. Objective: This study aims to analyze the relationship between child feeding practices and stunting in toddlers. Method: This study used a cross-sectional design conducted in the Oesao Community Health Center (Puskesmas Oesao) working area. The sample was 30 toddlers aged 6–59 months selected using a purposive sampling technique. Child feeding practices were measured using a structured questionnaire, while stunting status was determined based on the WHO standard length/height-for-age (PB/U or TB/U) index. Data analysis was performed univariately and bivariately using the Chi-Square test. Results: The results showed that most toddlers with inadequate feeding practices experienced stunting. Bivariate analysis showed a significant relationship between child feeding practices and stunting (p < 0.05). Conclusion: Child feeding practices are significantly associated with stunting in toddlers. It is necessary to increase nutritional education and support families in feeding children as an effort to prevent stunting.